PENGARUH LEVERAGE, KESEMPATAN TUMBUH, KEBIJAKAN DIVIDEN DAN LIKUIDITAS TERHADAP KEPUTUSAN HEDGING PT. UNILEVER TBK - Astyrianti, Nyoman Norita; Sudiartha, Gede Merta (E-Jurnal Manajemen; Vol 6 No 3 (2017), 2017)
ABSTRACT Multinational companies that conduc tinternational transactions will require hedging by using derivative instrument, in which the function is to minimize exchange rate risk faced by the company. The purpose of this study is to determine the effect of leverage, growth opportunit y , dividend policy and liquidity on Hedging decision of PT. Unilever Tbk 2008 – 2015period. This study use non-participant observation for data collection and analysis techniques of multiple linear regression which includes classical assumption and hypothesis testing using partial test and coefficient of determination. Based on the analysed data the results obtain are as follows, Leverage effect positively and significantly to hedgingdecision, company growth opportunit y has positive and significant effect hedging decision , dividend policy has negative and significant effect to hedging decision and l iquidity has positive and significantinfluence to hedging decision.
Keywords: hedging, derivative instrument, hedging decision